2006
DOI: 10.1002/marc.200500707
|View full text |Cite
|
Sign up to set email alerts
|

Styrene Emulsion Polymerization above the CMC: New Evidence on Particle Nucleation by means of AFFFF

Abstract: Summary: The number (N) and size distribution of particles (PSD) of a styrene emulsion polymerization above the CMC were studied by means of asymmetric flow‐field flow fractionation (AF4). Bimodal PSDs were obtained, suggesting that coagulation of the primary particles is not as extensive as would be expected, according to the coagulative mechanism. AF4 allowed it to be demonstrated that N is constant during interval II, and that the resolution limit of other particle sizing techniques can lead to erroneous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Emulsion polymerization with the least amount of water‐soluble monomers (e.g., carboxylic acids) prevents unwanted polymerization in the continuous phase and undesirable particle morphologies at the end of process and, hence, is most favorable 18. In addition, an excess amount of emulsifier, much higher than the critical micelle concentration, causes compact micellar structures and results in unbalanced dynamic transportation of monomers 19. Hence, we were not able to carry out experimental design item 6.…”
Section: Methodsmentioning
confidence: 99%
“…Emulsion polymerization with the least amount of water‐soluble monomers (e.g., carboxylic acids) prevents unwanted polymerization in the continuous phase and undesirable particle morphologies at the end of process and, hence, is most favorable 18. In addition, an excess amount of emulsifier, much higher than the critical micelle concentration, causes compact micellar structures and results in unbalanced dynamic transportation of monomers 19. Hence, we were not able to carry out experimental design item 6.…”
Section: Methodsmentioning
confidence: 99%
“…They further reported that the maximum seen in the rate of nucleation profile by Varela de la Rosa et al could be attributed to the increase in the average number of radicals in the particles with particle size. Furthermore, the experimental results of Carro and Herrera‐Ordonez61 allowed it to be demonstrated that the number of particles is constant during interval II. The same was reported earlier by Harada et al75…”
Section: Relative Importance Of Different Nucleation Mechanismsmentioning
confidence: 95%
“…Coagulation is also not included in this model. Carro and Herrera‐Ordonez's61 work on a styrene emulsion polymerization above cmc by means of AF 4 suggested that coagulation of the primary particles was not as extensive as would be expected according to the coagulative mechanism. My own theoretical work21 based on DLVO theory to calculate the minimum surfactant coverage required for stability against coagulation showed it to be 4.6% for two species having a hypergeometric diameter of 5 nm, which corresponds to the micellar dimensions.…”
Section: Relative Importance Of Different Nucleation Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation
“…The FFF separation mechanism does not rely on adsorption or partitioning making this technique less likely to suffer sample loss. In the 40 years since its inception, FFF has been used in numerous applications including the separation of nanotubes [10,11], stem and cancer cells [12,13], pathogenic microorganisms [14][15][16][17], parasites [18][19][20], inorganic and polymeric particles [21,22] and the study of processes such as cell apoptosis [23], surface adsorption [24][25][26], and hydrodynamic forces [27]. Two textbooks have been dedicated to FFF [28,29] and review articles continue to be published addressing polymers [30,31], proteins [32,33], biotechnology [34], and particles (to be published, Encyclopedia of Particle Technology http:// nanoparticles.org/encyclopedia/).…”
Section: Introductionmentioning
confidence: 99%